Pemanfaatan Desain Parametrik Dalam Perancangan Produk Keramik Dengan Visual Motif Tradisional (Studi Kasus: Hotel Best Western Premier La Grande) - Abdurrahman, Syaldilah Rizki (Universitas Komputer Indonesia, 2023)
The rapid increase in Indonesia's tourism sector has made many tourism-related business fields such as hotels to carry out various innovations in the creative field due to an increase in high competition. The habit of people who use hotels when traveling makes its function no longer only as an inn, but as part of traveling activities. The characteristics of the interior design and the elements in it greatly influence the interest of the people who prioritize aesthetics and comfort in choosing lodging. This research implements the Practice-led Research method with the flow of idea development, idea selection, data collection, and application of techniques as the process of applying the theories and methods chosen to create new products. The design of this ceramic product was carried out by adapting the basic form of the batik kawung pattern from the analysis of the character of the room in the case study and then implemented into a parametric design visual in the Grasshopper Rhinoceros 3D software. The output of this research is a recommendation for interior product design in the form of a wall hanging made of ceramic material that uses a modular concept with a visual approach to parametric design taken from the batik kawung pattern.